Imperial Irrigation District irrigation scheduling and event management pilot program - Fillmore, Darren R., author; Clark, Byron, author; Davids, Grant G., author; Eckhardt, John R., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2010)
The Imperial Irrigation District (IID) administered a pilot program in 2008 and 2009 to test various concepts proposed to fulfill its on-farm water conservation obligations under the Quantification Settlement Agreement. The program was intended to conserve about 1,000 ac-ft of water for payback of IID's Inadvertent Overruns in accordance with the Colorado River Water Delivery Agreement. Growers were invited to implement irrigation scheduling and event management for six months to conserve water relative to an ET-normalized, crop- and field-specific, historical water use baseline. Participants were required to hire an IID-qualified firm to provide irrigation scheduling and management recommendations, though they were not obligated to implement those recommendations. Upon enrollment, participating growers received a payment to fund a contract with a scheduling firm and to help defray some irrigation management costs. After the contract period, eligible participants received an additional payment based on the volume of water conserved. The program resulted in water savings of 0.1 – 1.2 ac-ft/ac on most of the 24 enrolled fields, though some fields used more water than their estimated, historical baseline.
USCID water management conference
Imperial Irrigation District pilot program
Presented at Upgrading technology and infrastructure in a finance-challenged economy: a USCID water management conference held on March 23-26, 2010 in Sacramento, California.